Comparison of compositional changes in multi-species grass/legume mixture experiments across three Nordic countries (Iceland, Sweden and Finland) over two years - Brophy, C.; Gustavsson, A.M.; Helgadottir, Aslaug; Nissinen, Oiva; Connolly, J. (Wageningen Academic Pub., 2005)
v ok